Loss in acoustic metasurfaces: a blessing in disguise. (March 2020) - Gerard, Nikhil JRK; Jing, Yun
Abstract: Abstract : From being an unfavorable consequence to finding itself as the intended imaginary part of a non-Hermitian system, loss has truly emerged as more of a friend than a foe in the context of acoustic metasurfaces. With the promising features of sub-wavelength geometries and the rapid advances in manufacturing techniques that can enable their realization, loss becomes a central topic of discussion. Further, the capability of introducing and tailoring loss allows it to serve as a new degree of freedom in passive wavefront shaping devices. In this review, the authors look back at the recent progress in the field of lossy acoustic metasurfaces. The background behind loss in deep sub-wavelength geometries and the instinctive responses to treat them and exploit them are overviewed, followed by more recent works that embrace and tailor their behavior for unconventional applications. The forthcoming years for acoustic metasurfaces thus hold several promising avenues for exploration, with loss as the protagonist.